AN OVERVIEW OF KNOWLEDGE LEVEL REGARDING THE SYSTEMIC LUPUS ERYTHEMATOSUS (SLE) IN PEOPLE WITH LUPUS (ODAPUS) - Farah Azwinda; Lilik Djuari; Gatot Soegiarto (The Indonesian Journal of Public Health, 2022)
Introduction: Systemic Lupus Erythematosus (SLE) is lay disease in Indonesia. People with lupus must undergo lifelong treatment because the manifestations vary with high mortality rate. The aim of this study is to measure the level of knowledge of ODAPUS about SLE.  Methods: This study was an observational descriptive with a cross-sectional approach.  One hundred respondents were selected consecutively according to inclusion criteria from SLE patients who attended outpatients of Rheumatology Polyclinic in RSUD (Regional Public Hospital) Dr. Soetomo Surabaya from September 2019 to January 2020. The variable was knowledge level of ODAPUS about SLE and ODAPUS characteristics. Data analysis used descriptive statistical analysis. Data were obtained using LKQ-R questionnaires. Result: The result showed that majority of respondents are female (95%), aged 17-25 years (34%), had Senior High School (SHS) as their highest educational background (60%), do not work (53%), got the information about SLE only from health services (71%), and had lack knowledge about SLE (68%). There is no difference between knowledge about SLE in gender (p-value 0.123), a significant relationship between knowledge and educational background (p-value 0.005), and  differences in the level of knowledge in group of information sources (p-value  0,000). Conclusion: In conclusion, most of the SLE patients have lack of knowledge about SLE, especially those who have SHS educational background and only depend on the health service as the source of information. Special interventions are needed as health promotion, especially in childbearing age women who likely suffer from the disease.